Effect of Leadership, Compensation, and Culture on Employee Productivity: Pengaruh Kepemimpinan, Kompensasi, dan Budaya terhadap Produktivitas Karyawan - Alsya, Nova Firda; Ubaidillah, Hasan (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the impact of leadership, compensation, and organizational culture on employee productivity at PT. Romi Violeta in Sidoarjo, East Java. Using a quantitative approach with multiple linear regression analysis via SPSS version 25, data from 95 randomly sampled employees were analyzed. The results indicate that while leadership does not significantly affect productivity, compensation and organizational culture positively and significantly do. Additionally, these variables collectively enhance employee productivity, with compensation being the most influential. These findings suggest that improving compensation and fostering a strong organizational culture are crucial for boosting productivity. Highlight: Leadership does not significantly impact employee productivity. Compensation and organizational culture positively affect productivity. Simultaneous effects of leadership, compensation, and culture are significant. Keywords: Leadership, Compensation, Organizational Culture, Employee Productivity, Quantitative Research